Metal–Organic‐Framework‐Derived Dual Metal‐ and Nitrogen‐Doped Carbon as Efficient and Robust Oxygen Reduction Reaction Catalysts for Microbial Fuel Cells. Issue 2 (3rd December 2015) - Tang, Haolin; Cai, Shichang; Xie, Shilei; Wang, Zhengbang; Tong, Yexiang; Pan, Mu; Lu, Xihong
Abstract : A new class of dual metal and N doped carbon catalysts with well‐defined porous structure derived from metal–organic frameworks (MOFs) has been developed as a high‐performance electrocatalyst for oxygen reduction reaction (ORR). Furthermore, the microbial fuel cell (MFC) device based on the as‐prepared Ni/Co and N codoped carbon as air cathode catalyst achieves a maximum power density of 4335.6 mW m −2 and excellent durability.